The Role of Tourist Attitude Toward Destination Awareness, Destination Personality And Future Visit İntention - Ersy Ervina; Vany Octaviany (Department of Management, Faculty of Economics and Business, Brawijaya University, 2022)
Creating tourist visit intention in the future is a challenge for tourism industry, but lack attention of the evaluation how tourist attitude mediating destination awareness and destination personality on future visit intention. This paper aims to analyze the direct and indirect effects of destination awareness and destination personality on future visit intention with the mediating role of tourist attitude. A quantitative technique utilizing a questionnaire is utilized to gather data. The Lameshow sampling method was used to acquire a sample of 100 respondents for this investigation. The data analysed using the Partial Least Squares Structural Equation Model (PLS-SEM). Result obtained destination awareness and destination personality have a positive effect on tourist attitude. Destination personality also has a positive effect on future visit intention. Meanwhile, destination awareness has a positive but not significant effect on future visit intention. The findings of this study show that tourists' positive attitudes play a key role in bridging the gap between destination awareness and destination personality in terms of future visit intentions. Repeat visits in the future will be more beneficial if a destination takes initiatives to influence tourists' positive attitudes, particularly on destination awareness. Futures study might cover the service industry, with a comparison utilizing the suggested model. Furthermore, the intended model might be confirmed by gathering data from a large number of respondents. These results provide new theoretical and practical implications for tourism destination marketing and policymakers